Analisis Analisis Pengembangan Desa Wisata dengan Kerawanan Tanah Longsor di Nagari Gunuang Rajo - Pratama, Viki Aulia; Prarikeslan, widya (JURNAL BUANA, 2026)
Nagari Gunuang Rajo has tourism potential such as special interest tourism, religious tourism, nature tourism and culinary tourism. Apart from that, BNPB designated Nagari Gunuang Rajo as a disaster resilient village because it is prone to landslides. Therefore, a strategy for developing tourist areas was formulated to minimize the risk of disasters in tourist areas. This research is a mixed method, participatory mapping analysis techniques, AHP analysis, and SWOT analysis. The results of map of the tourism show that infrastructure facilities at Gunuang Rajo Tourism Village such as roads, places of worship, health facilities, offices, homestays, motorbike taxi bases, MSMEs and tourist attractions. Apart from that, the potential landslide vulnerability map shows a green zone of 331.81 Ha, a yellow zone of 245.64 Ha, and a red zone of 104.50 Ha. The strategy for developing Gunuang Rajo Tourism Village is resolving land use permit issues, infrastructure development, increasing tourism understanding, developing durian processing, implementing disaster resilience programs, socializing landslide disasters, and developing tourist attractions into green zones.